Carbon‐supported AuPt and AuPd bimetallic nanocomposites as formic acid electrooxidation catalysts. Issue 12 (3rd September 2015) - Lewis, Sharlene A.; Wilburn, Jeremy P.; Wellons, Matthew S.; Cliffel, David E.; Lukehart, Charles M.
Abstract : Repetitive syntheses of six AuPt/Vulcan carbon (VC) and six AuPd/VC nanocomposites by NaBH4 solution reduction of equimolar mixtures of HAuCl4  ·  x H2 O and H2 PtCl6  · 6H2 O salts or HAuCl4  ·  x H2 O and Na2 PdCl4 salts gives nanocomposites having highly dispersed metal alloy nanoparticles of similar average size (4–7 ± 2 nm). Significant variation in nanocomposite physical and electrochemical properties is observed. AuM alloy stoichiometries and total metal wt% vary by as much as ±11 at% and ±5 wt%, respectively. Activities toward electrocatalytic oxidation of formic acid, evaluated by cyclic voltammetry, reveal one electrochemically inactive nanocomposite, higher activities for AuPd/VC nanocomposites than for AuPt/VC nanocomposites, and a maximum mass‐specific current of 3.8 mA cm −2 per mg total metal for one AuPd/VC nancomposite. TEM image of AuPt/Vulcan carbon (left image) and AuPd/Vulcan carbon (right image) nanocomposites. Bar represents 20 nm.